Pengaruh Enterprise Risk Management, dan Likuiditas Terhadap Economic Performance - Nur ‘Aini Qurrota A’yun; Dirvi Surya Abbas; Kimsen Kimsen (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study is to determine the effect of enterprise risk management, and liquidity on economic performance. The study is time period used was 5 years, namely the 2017-2021 period. The population of this study includes all food and beverages sector companies listed on the Indonesia Stock Exchange (BEI) for the 2017-20201 period. The sampling technique uses purposive sampling technique. Based on the predetermined criteria, 10 companies were obtained. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The analytical method used is panel data regression analysis using Eviews 9. The results showed that variables enterprise risk management had a positive impact on economic performance, while the liquidity variable do not affect economic performance.